PENGEMBANGAN MODEL SISMS SEBAGAI SOLUSI INTEGRATIF PENDIDIKAN BERBASIS IMAN DAN TEKNOLOGI - Yusuf, M.; Goffar, Abdul (An-Nahdliyyah: Jurnal Studi Keislaman, 2025)
This study aims to develop the concept of the Smart Islamic School Management System (SISMS) as a management model for Islamic education that harmoniously integrates faith-based values with digital technological advancement. Using a library research approach, this study reviews relevant literature on Islamic education management, smart school systems, and the integration between spirituality and technological innovation. The literature analysis reveals a significant gap in implementing Islamic values within digital-based management systems in educational institutions. Therefore, SISMS is proposed as a conceptual model that balances administrative efficiency with Islamic spiritual principles through three key dimensions: managerial spirituality, data-driven governance, and ethical Islamic leadership. This model not only emphasizes professionalism and institutional performance effectiveness but also fosters blessing-oriented outcomes, moral responsibility, and a work culture grounded in faith. The findings imply that SISMS can serve as a new direction for the transformation of Islamic education management, creating a balanced synthesis between modern technological systems and the essential spiritual mission of Islamic education.